The Mla pathway promotes Vibrio cholerae re-expansion from stationary phase - Deborah R. Leitner; Franz G. Zingl; Alexander A. Morano; Hailong Zhang; Matthew K. Waldor (mBio)
ABSTRACT Bacteria have evolved diverse strategies to ensure survival under nutrient-limited conditions, where rapid energy generation is not achievable. Here, we performed a transposon insertion site sequencing loss-of-function screen to identify Vibrio cholerae genes that promote pathogen fitness in stationary phase. We discovered that the maintenance of lipid asymmetry (Mla) pathway, which is crucial for transferring phospholipids from the outer to the inner membrane, is critical for stationary phase fitness. Competition experiments with barcoded and fluorophore labeled wild-type (WT) and mlaE mutant V. cholerae revealed that the Mla pathway promotes re-expansion from 48 h stationary phase cultures. The mutant defect in transitioning out of stationary phase into active growth (culturability) was also observed in monocultures at 48 h. However, by 96 h the culturability of the WT and mutant strains were equivalent. By monitoring the abundances of genomically barcoded libraries of WT and ∆mlaE strains, we observed that a few barcodes dominated the mutant culture at 96 h, suggesting that the similarity of the population sizes at this time was caused by expansion of a subpopulation containing a mutation that suppressed the defect of ∆mlaE. Whole genome sequencing revealed that mlaE suppressors inactivated flagellar biosynthesis. Additional mechanistic studies support the idea that the Mla pathway is critical for maintaining the culturability of V. cholerae because it promotes energy homeostasis, likely due to its role in regulating outer membrane vesicle shedding. Together our findings provide insights into the cellular processes that control re-expansion from stationary phase and demonstrate a previously undiscovered role for the Mla pathway.IMPORTANCEBacteria regularly encounter conditions with nutrient scarcity, where cell growth and division are minimal. Knowledge of the pathways that enable re-growth following nutrient restriction is limited. Here, using the cholera pathogen, we uncovered a role for the Mla pathway, a system that enables phospholipid re-cycling, in promoting Vibrio cholerae re-expansion from stationary phase cultures. Cells labeled with DNA barcodes or fluorophores were useful to demonstrate that though the abundances of wild-type and Mla mutant cells were similar in stationary phase cultures, they had marked differences in their capacities to regrow on plates. Of note, Mla mutant cells lose cell envelope components including high-energy phospholipids due to OMV shedding. Our findings suggest that the defects in cellular energy homeostasis that emerge in the absence of the Mla pathway underlie its importance in maintaining V. cholerae culturability.